Importance of gradients in membrane properties and electrical coupling in sinoatrial node pacing. - Shin Inada; Henggui Zhang; James O Tellez; Nitaro Shibata; Kazuo Nakazawa; Kaichiro Kamiya; Itsuo Kodama; Kazuyuki Mitsui; Halina Dobrzynski; Mark R Boyett; Haruo Honjo (PLoS ONE)
The sinoatrial node (SAN) is heterogeneous in terms of cell size, ion channels, current densities, connexins and electrical coupling. For example, Nav1.5 (responsible for INa) and Cx43 (responsible for electrical coupling) are absent from the centre of the SAN (normally the leading pacemaker site), but present in the periphery (at SAN-atrial muscle junction). To test whether the heterogeneity is important for the functioning of the SAN, one- and two-dimensional models of the SAN and surrounding atrial muscle were created. Normal functioning of the SAN (in terms of cycle length, position of leading pacemaker site, conduction times, activation and repolarization sequences and space constants) was observed when, from the centre to the periphery, (i) cell characteristics (cell size and ionic current densities) were changed in a gradient fashion from a central-type (lacking INa) to a peripheral-type (possessing INa) and (ii) coupling conductance was increased in a gradient fashion. We conclude that the heterogeneous nature of the node is important for its normal functioning. The presence of Nav1.5 and Cx43 in the periphery may be essential for the node to be able to drive the atrial muscle: Nav1.5 provides the necessary depolarizing current and Cx43 delivers it to the atrial muscle.